Development of Web-Based Multimedia Learning for Grade 3 Elementary School Mathematics - Muharom, Ahmad; Rukhviyanti, Novi (P3M Politeknik Negeri Bengkalis, 2025)
The development of information technology has significantly contributed to the education sector, particularly in creating interactive and engaging learning media. Mathematics, as one of the core subjects, is often perceived as difficult and tedious by students. Therefore, there is a need for innovative learning media that can enhance students’ interest and understanding of the subject matter. This study aims to design and implement an interactive mathematics game website that presents basic math problems in an enjoyable and responsive format. The website consists of nine pages, including a landing page, login, dashboard, quiz selection, quiz display, and evaluation results. Each quiz contains 10 questions displayed in two horizontal rows (5 questions each), supported by a countdown timer and an automatic scoring system. The development methodology includes needs analysis, system design, implementation, and evaluation. The evaluation phase was conducted through internal testing and user observation targeting elementary school students.